4,4-Dimethyl-3,4-dihydropyrido[2',3':3,4]pyrazolo[1,5-a ][1,3,5]triazin-2-amine ethanol monosolvate - Dolzhenko, Anton; Tan, G.; Dolzhenko, A.; Koh, L.; Chui, W. (Blackwell Munksgaard, 2011)
In the title compound, C10H12N6.C2H5OH, the planarity of the heterocyclic system is slightly distorted at the triazine ring (r.m.s. deviation = 0.1191 A), which adopts a conformation best described as intermediate between a flattened twisted boat and a half-boat with the tertiary Csp3 atom at the bow. In the crystal, molecules form centrosymmetric dimers connected by N...H-O and O...H-N hydrogen bonds between the amino group H atom, the ethanol solvent molecule and the triazine N atom, making an R4 4(12) graph-set motif. The other H atom of the amino group and the H atom on the endocyclic N atom form N...H-N hydrogen bonds with the N atoms of the pyrazole and pyridine rings, respectively, linking the molecules into C(7)C(7) chains with the R2 2(8) binary graph-set motif running along [010].